Zimbabwean commercial banks liquidity risk determinants after dollarisation - Chikoko, Laurine (Scienpress Ltd, 2015)
The government of Zimbabwe adopted a multiple currency regime in January 2009 after a decade of economic decline. The new regime brought with it benefits to the economy and helped restart financial intermediation. Despite these benefits, many banks are facing challenges of liquidity risk. This paper empirically investigates the determinants of Zimbabwean commercial banks liquidity risk after the country adopted the use of multiple currencies exchange rate system. To do so, panel data regression analysis is used on monthly data from March 2009 to December 2012. From the panel data regression results, capital adequacy and size have negative significant influence on liquidity risk. As size increases, liquidity risk reduces. Spreads have positive influence on liquidity risk. Non-performing loans have a positive significant relationship with liquidity risk. Reserve requirement ratios and inflation were also significant in explaining liquidity risk during the studied period. For commercial banks to manage liquidity risk there is need to pay attention to bank capitalisation, the size of the bank and on the differences between the deposit rates and lending rates. There is also need for improved credit risk analysis if banks are to have good financial assets in the dollarised environment.